ANALISIS KUALITAS PELAYANAN AKADEMIK DAN KUALITAS KINERJA DOSEN TERHADAP KEPUASAN MAHASISWA DI UNDHARI: ANALISIS KUALITAS PELAYANAN AKADEMIK DAN KUALITAS KINERJA DOSEN TERHADAP KEPUASAN MAHASISWA DI UNDHARI - Elfita Amalia (International Journal of Management and Business (IJMB), 2022)
This research was conducted to find out and analyze the impact of Service Quality and Lecturer Performance Quality on Student Satisfaction at Undhari.The purpose of this study was to determine and analyze "Analysis of Service Quality and Lecturer Performance Quality on Student Satisfaction at Undhari (Case Study of Students at Undhari in 2021)"This research method uses quantitative analysis techniques using questionnaires. This research is about analyzing the quality of academic services and the quality of lecturers on student satisfaction in Undhari. The sample respondents were 309 students, consisting of 33 FIKES students, 80 FILKOM students, 162 FKIP students, and 34 FHEB students.From the results of the study, it can be seen that simultaneously / together there can be a positive and significant influence between the Quality of Academic Service and the Quality of Lecturer Performance on Student Satisfaction at Undhari, with an R coefficient value of 0.760 and an Adjusted R Square coefficient of 0.644. The simultaneous contribution between the variables of Academic Service Quality and Lecturer Performance Quality on Student Satisfaction is 64.4%, and the other 35.6% is influenced by other variables not examined such as climate, location, work discipline, motivation, work organizational structure, rules and regulations. work, leadership style, and others.Academic Service Quality has a big effect on Student Satisfaction. the more the quality of academic services is improved, the better it will have on student satisfaction at Undhari.